Raising entrepreneurial capital - Vinturella, John B., 1942- (Elsevier insights., 2013)
This book guides the reader through the stages of successfully financing a business. It proceeds from a basic level of business knowledge, assuming that the reader understands simple financial statements, has selected a specific business, and knows how to write a business plan. It also covers worldwide variations in forms and availability of pre-seed capital, incubators, and the business plans they create, with case studies from Europe, Latin America, and the Pacific Rim.